PROBLEM BASED LEARNING MODEL ON MATH SUBJECT TO INCREASE STUDENT’ LEARNING OUTCOMES AT GRADE V SDN 05 PADANG PASIR - Imam Taufiq; Elvia Sukma; Tri Susilawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the fact that students’ mathematics learning outcomes at grade V of SDN 05 Padang Pasir, Padang were still low. This was due to the covid-19 pandemic that hit Indonesia and the learning model which was suitable to the students’ characteristics had not been applied. The purpose of this research was to describe the application of Problem Based Learning (PBL) learning model to improve students’ learning outcomes at grade V of SDN 05 Padang Pasir, Padang. The type of this research was Classroom Action Research using qualitative and quantitative approaches. Research procedures included planning, implementation, observation, and reflection. Research data were obtained from observations and actions as well as test results. The source of data was the process and results of the implementation of learning by using PBL model on data processing material. This research was conducted in Semester II of the academic year 2020/2021. The research subjects were a teacher as the observer, the researcher as the practitioner, and grade V students as many as 25 people. The results showed an increase in the average of students’ learning outcomes in Cycle I from 68.95 to 87.8 in Cycle II. The results of the RPP observations increased from 88.9% in Cycle I to 100% in Cycle II. The results of observations for the teacher’s and students’ aspects in Cycle I were 75% and increased to 100% in Cycle II. It was concluded that the PBL model improved the mathematics learning outcomes of data processing materials at grade V of SDN 05 Padang Pasir, Padang.